Overview of Demographic Evolution in Romania - Valentina VASILE; Ana Maria DOBRE (Revista Română de Statistică, 2015)
The aim of this paper is to analyze the demographic evolution of Romanian population in the last two decades, based on census data and to define main challenges on labour market potential and professional profile. We are referring to aspects of the general demographic characteristics, ethnic composition and age dependency ratios of Romanian resident population. The empirical research was completed by data visualization of demographic data, using R software. Based on this analysis, we are advancing some signals on the effects produced by the demographic structure dynamics in the last decades on specific groups of population, like school population and working-age population.